An observational study of incidence of metabolic syndrome among patients with controlled Grave's disease - Jinesh Sengupta; Himadri Das; Vinoth Gnana Chellaiyan D; Sasithra S; Jennifer Britto J (Elsevier, 2022)
Background: Graves disease is one of the most common autoimmune diseases affecting Indians, accounting for 50-80% of hyperthyroidism cases. The major morbidities associated with Graves' disease are universally acknowledged. Thus, preventing metabolic syndrome could lead to a reduction in the country's disease burden. Objectives: The objectives of this study are to determine the detection of metabolic syndrome in patients who have achieved clinical and biochemical euthyroid status after treatment, as well as to evaluate the clinical and biochemical parameters that lead to metabolic syndrome in Graves' disease patients. Materials and methods: This is a prospective observational study of 96 Graves' disease patients in a tertiary care hospital in rural Kolkata. The study participants were chosen using systemic random sampling. The clinical and biochemical parameters of the participants in the study were evaluated. The paired t tests were used. A P value of 0.05 is regarded as significant. Results: After achieving euthyroid status, 36% of the study population developed metabolic syndrome according to International Diabetes Federation (IDF) criteria.93.5% of those who developed metabolic syndrome had a normal BMI at the time of Graves' disease diagnosis. Conclusion: Following a healthy lifestyle, which includes healthy eating habits, proper drug compliance, and follow-up, may help to prevent the occurrence of metabolic syndrome. By lowering the risk of developing metabolic syndrome, patients may be able to live a healthier lifestyle by keeping the disease under control.